El apego y su relación con el aprendizaje de los niños y niñas del primer grado, de la “escuela de educación básica “FÁE” del sector Puerto Aguarico, provincia Sucumbíos, cantón Lago Agrio, parroquia Nueva Loja, período lectivo 2013-2014 - Herrera Garcés, Andrea Isabel (2014)
This thesis refers to THE ADDICTION AND ITS RELATIONSHIP WITH LEARNING OF CHILDREN, THE FIRST GRADE OF "BASIC EDUCATION SCHOOL "FAE‖ PUERTO AGUARICO SECTOR, PROVINCE SUCUMBÍOS, SOUR LAKE CANTON, NEW PARISH LOJA. LECTIVO PERIOD, 2013-2014. "GUIDELINES PROACTIVE. The general objective was to: Determine the Attachment and its relation to learning children, First Grade, "School Basic Education" FAE "Puerto Aguarico sector, Sucumbios province, canton Lago Agrio, Nueva Loja parish. The methods used for the preparation of this research work were Scientist, Analytical, Synthetic, Inductive, Deductive, Descriptive and Statistical Model, which served them help efficiently achieve the goal. The techniques and instruments used were an Observation Form applied to children to identify the type of attachment to their mothers and Observation Guide for children to evaluate learning. In the implementation of the Observation Form to children concluded that: 91% of children have observed Secure Attachment, 9% do not have Secure Attachment; 63% of children have observed avoidant, 37% do not have Avoidant Attachment, 64% of children do not have an ambivalent attachment, 36% do show an ambivalent attachment, 96% of children and girls do have a disorganized attachment, 4% not having a disorganized attachment. From the results obtained in the Observation Guide is concluded that: 76% of the children assessed are rated on their level as a very outstanding in the learning activities, 20% of children are outstanding as rated their level of learning in the activities, and 5% of children have a low level of learning in their outstanding activities performed.